Emotion dysregulation mediates the relationship between trauma type and PTSD symptoms in a diverse trauma-exposed clinical sample. (1st March 2019) - Raudales, Alexa M.; Short, Nicole A.; Schmidt, Norman B.
Abstract: Background: Research has explored the influence of trauma type on emotion dysregulation and the role of emotion dysregulation in posttraumatic stress disorder (PTSD). However, it remains unclear whether trauma types differentially impact emotion dysregulation, and whether this in turn contributes to elevated PTSD. The current study tested whether trauma type is related to PTSD symptoms via emotion dysregulation. Methods: Trauma-exposed community members ( n = 209) completed a semi-structured clinical interview and self-reported on emotion regulation, trauma exposure, PTSD symptoms, and negative affect. Results: Interpersonal trauma, sexual assault in particular, is associated with greater emotion dysregulation. Furthermore, emotion dysregulation mediates the effects of trauma type on PTSD symptoms for sexual assault but not other trauma types, and effects remained significant after covarying for negative affectivity. More recent and chronic trauma was not associated with greater emotion dysregulation. Conclusions: This study underscores the importance of emotion dysregulation in PTSD development and maintenance. Findings may be used for the development of interventions targeting emotion regulation as a malleable risk factor for PTSD, especially for sexual assault victims.